NURSING STUDENTS' EXPERIENCES OF INTERACTING WITH MENTORS IN CLINICAL PRACTICE - Žilionytė, Aušrinė; Sabaliauskas, Stanislav; Stirblienė, Jurgita (Slauga. Mokslas ir praktika, 2023)
Nursing mentorships in Lithuania are not quite as well researched compared to other European nations. Good mentor-pupil relations make a huge difference in the quality of studies. Mentors that care, and invest more time in the students themselves, correlate with better student reviews and overall satisfaction in practical works.The aim of the study was to investigate nursing students' experiences of interacting with mentors in clinical practice by analysing the results of research studies. A systematic review of the scientific literature was conducted.Results and conclusions. The results showed that during the COVID-19 pandemic, mentors spent significantly less time with students during their placements, which had an impact on the quality of placements. It also came to be, that during the pandemic, students were used as additional working hands, and would shadow various hospital employees as opposed to the assigned mentors. Generally speaking, students tend to complain of a lack of personal connection with said mentors, with an underlying difficulty of bringing up personal problems and concerns. However, there are also students that are at ease with the quality of their studies, and with the mentors that assist them grow in the working environment. When discussing studies within the hospital/health setting, formation of good habits are appropriate for the students and mentors alike.
Keywords: nursing students; mentors; clinical practice; communication; relationships; experience